History Man behind the Legends: Tracing Golwalkar$1 (Bs Path to Powers - Reviewed by Amol Saghar (The Book Review)
Jha, Dhirendra K. Golwalkar: The myth behind the man, The man behind the machine: Simon & Schuster, 2024, 385p. Rs. 899.00